Two-dimensional vacancy-doped MXene nanomaterials for supercapacitors - Yi Tang; Zhao Bi; Yangyang Xie; Xiaodie Xuan; Chenhui Yang (Frontiers in Chemistry)
Supercapacitors (SCs) are high-performance electrochemical energy storage devices, and their performance hinges on the electrode materials. 2D MXene nanomaterials, with their excellent conductivity, tunable interlayer spacing, and rich surface chemistry, have emerged as highly promising electrode materials for SCs. However, the capacitive performance of intrinsic MXene fails to meet application requirements. This review first introduces the composition and principles of SCs in detail, then summarizes the pure MXene nanomaterials in SCs, and systematically explores the regulatory mechanisms of vacancy doping strategies on MXene material structure and capacitive performance. The study reveals the structure-property relationships, providing theoretical basis and direction for designing high-performance MXene-based SCs electrode materials.